RETRACTED; Episodic Memory: A Comparative Approach - Martin-Ordas, Gema; Call, Josep (Frontiers in Behavioral Neuroscience, 2013)
Historically, episodic memory has been described as autonoetic, personally relevant, complex, context-rich, and allowing mental time travel. In contrast, semantic memory, which is theorized to be free of context and personal relevance, is noetic and consists of general knowledge of facts about the world. The field of comparative psychology has certainly adopted this distinction in order to study episodic memory in non-human animals. Our aim in this article is not only to reflect on the concept of episodic memory and the experimental approaches used in comparative psychology to study this phenomenon, but also to provide a critical analysis of these paradigms. We conclude the article by providing new avenues for future research.